Santri Character Development (Primary Age Children) Through the Tahfidzul Qur'an Program - Yudistira Fuady; Siti Halimah; Haidir Haidir (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe efforts to develop the character of elementary-aged students through the tahfidz al-Qur'an program at the Tahfidzul Qur'an Al Fawwaz Foundation in Medan. This study uses a qualitative approach with a descriptive study method. Collecting data sources through interviews, observations, and documentation. Sources of data or informants are the foundation, parents of students and students from the foundation. While checking the validity of the data is done through the degree of trust (credibility), transferability, dependability, and certainty (confirmability). The results of this study conclude that: first, the implementation of character building in the tahfidz Al-Qur'an program is guided by the vision and mission of the Tahfidzul Qur'an Al-Fawwaz Foundation, while the implementation process goes through three stages, namely the tahsin activity program (reading improvement), tasmi' (memorization deposit), and muraja'ah (repeating rote) activities. As for the strategy, and evaluation through three approaches, namely teacher example, habituation, and tahfiz. Second, aspects of character building in the Al-Qur'an tahfidz program at the Al-Fawwaz Tahfidzul Qur'an Foundation, among others; religious aspects, discipline, willingness, hard work, and responsibility. Third, the successful implementation of character education in the Tahfidz Al-Qur'an program at the Tahfidzul Qur'an Al-Fawwaz Foundation, namely, First: the embedded values of religious character, discipline, high will, hard work, and responsibility of students. Second: the students' memorization achievement continues to increase.